"ETHNOGRAPHER EUGENE SCHILLING AND HIS LEGACY": CULTURAL AND EDUCATIONAL PROJECT. CHRONICLE OF EVENTS - Petenina, Tat'ana Pavlovna (History, Archeology and Ethnography of the Caucasus, 2019)
As part of the cultural and educational project “Ethnographer Yevgeny Shilling and his legacy” several scientific and public events were held in the republic. The article is a brief overview of the conference, reports on the participants, subjects of scientific reports and other activities to perpetuate memory of the founder of the Soviet Dagestan studies.
Keywords: Yevgeny Mikhailovich Shilling; ethnography; caucasiologist; conference; traditional culture; ornamental art; Dagestan; Kubachi.